RENEWABLE ENERGY AND TRADE DISPUTES: IMPLICATIONS ON SOLAR PHOTOVOLTAIC MANUFACTURING IN MALAYSIA - Hui, Nee Au Yong; Kock, Lim Tan (PLANNING MALAYSIA, 2017)
Malaysia has realised the importance of renewable energy (RE) in the energy mix and continuously reviewing its energy policy to ensure sustainable energy supply. The use of RE is among the options although the RE capacity is still underutilized. Malaysia achieves 5.5% share of RE in the energy mix by 2015, and the RE sector is expected to double by 2020 with strong growth in the solar photovoltaic (PV), biomass and biogas markets. Beyond 2020, it is predicted that solar energy will surpass all other forms of RE for Malaysia and other countries, and the solar power will be the long term source of energy supply. After an investigation on the RE policy, the domestic solar PV manufacturing scenario is elaborated in this paper. This includes the solar PV manufacturing, issues and trade disputes, and the way forward. Among the key findings from this paper include: the foreign direct investment (FDI) related to RE sector especially from the US and lately China, have increased rapidly, and more â€˜green’ jobs in the solar PV manufacturing and installation sectors have been created. With the existence of trade disputes between the United States and the European Union with China, Malaysia has the potential to reap benefits with the inflow of direct investments from China. Nevertheless, the future incidence of RE trade disputes is still uncertain.